Optimalisasi Legalitas Usaha Melalui Layanan OSS dan Digitalisasi Keuangan dengan Aplikasi Teman Bisnis pada UMKM - Pranandisya, Nindya; Wafa, Zaenal (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The implementation of activities is carried out in MSMEs in the food and beverage sector. MSMEs as businesses that affect the economy in Indonesia need a review of business legality for business development. Currently, MSMEs still lack knowledge of the importance of business legality ownership so many MSMEs do not have legality. This activity is carried out to provide knowledge and assist in the process of making business legality such as NIB, halal certification. Another activity is digital bookkeeping which is also an obstacle for MSMEs that are still recording manually. The method used is socialization of the importance of legality and bookkeeping as well as assistance in making NIB, halal certificates, and digital bookkeeping using the Teman Bisnis application. The results of this activity are that MSMEs can recognize the importance of legality for their business, MSMEs already have business legality such as NIB, halal certificate processes, and have digital-based financial bookkeeping.